Sequential activation and inactivation of Dishevelled in the Wnt/beta-catenin pathway by casein kinases - Bernatik, Ondrej; Ganji, Ranjani Sri; Dijksterhuis, Jacomijn P; Konik, Peter; Cervenka, Igor; Polonio, Tilman; Krejci, Pavel; Schulte, Gunnar; Bryja, Vitezslav (The Journal of biological chemistry, 2011)
Dishevelled (Dvl) is a key component in the Wnt/β-catenin signaling pathway. Dvl can multimerize to form dynamic protein aggregates, which are required for the activation of downstream signaling. Upon pathway activation by Wnts, Dvl becomes phosphorylated to yield phosphorylated and shifted (PS) Dvl. Both activation of Dvl in Wnt/β-catenin signaling and Wnt-induced PS-Dvl formation are dependent on casein kinase 1 (CK1) δ/ε activity. However, the overexpression of CK1 was shown to dissolve Dvl aggregates, and endogenous PS-Dvl forms irrespective of whether or not the activating Wnt triggers the Wnt/β-catenin pathway. Using a combination of gain-of-function, loss-of-function, and domain mapping approaches, we attempted to solve this discrepancy regarding the role of CK1ε in Dvl biology. We analyzed mutual interaction of CK1δ/ε and two other Dvl kinases, CK2 and PAR1, in the Wnt/β-catenin pathway. We show that CK2 acts as a constitutive kinase whose activity is required for the further action of CK1ε. Furthermore, we demonstrate that the two consequences of CK1ε phosphorylation are separated both spatially and functionally; first, CK1ε-mediated induction of TCF/LEF-driven transcription (associated with dynamic recruitment of Axin1) is mediated via a PDZ-proline-rich region of Dvl. Second, CK1ε-mediated formation of PS-Dvl is mediated by the Dvl3 C terminus. Furthermore, we demonstrate with several methods that PS-Dvl has decreased ability to polymerize with other Dvls and could, thus, act as the inactive signaling intermediate. We propose a multistep and multikinase model for Dvl activation in the Wnt/β-catenin pathway that uncovers a built-in de-activation mechanism that is triggered by activating phosphorylation of Dvl by CK1δ/ε.
Keywords: signální transdukce; Phosphorylation; Signal Transduction; kaseinkinasa Iepsilon; Humans; kaseinkinasa Idelta; fosfoproteiny; proteiny Wnt; fosforylace; beta-katenin; Peptide Mapping; adaptorové proteiny signální transdukční; Receptor, PAR-1; Wnt Proteins; lidé; Casein Kinase II; Adaptor Proteins, Signal Transducing; zvířata; HEK293 Cells; myši; Casein Kinase 1 epsilon; peptidové mapování; Mice; Dishevelled Proteins; protein dishevelled; HEK293 buňky; kaseinkinasa II; beta Catenin; receptor PAR-1; Animals; Phosphoproteins; Casein Kinase Idelta